APLIKASI PELAYANAN KARTU PAS DI BANDARA HANG NADIM BATAM BERBASIS WEB - Saputra, Dedy; Yenni, Yusli (LPPM Universitas Putera Batam, 2021)
With the status of an international airport and the size of this airport, the airport enforces a policy, namely that every area in Hang Nadim Airport has certain access restrictions. Airport employees can pass through or enter several vital areas of the airport, in contrast to shopkeepers or tenants, cargo employees, and airline employees, they cannot enter the airport area freely, usually all workers at the airport have certain area restrictions on the card The airport's Public Address System (PAS) is used and has been determined. The objectives and expectations of this research are to analyze the needs, design, and implement a web- based PAS card service system at Hang Nadim airport. By determining the system design method used by researchers in making this research, namely the Waterfall method, and concluding that, the pass card service system at Hang Nadim Airport Batam currently has too many unnecessary procedures, which makes the bureaucratic process of making existing pass cards. In that place it seems convoluted. With the new system it is hoped that it can cut more unnecessary time and procedures, and the application of web-based PAS card services at Batam Hang Nadim airport which is designed is expected to simplify the process of making the pass card itself, as well as the implementation process at Batam Hang Nadim Airport. Done by installing software and also the required hardware and a system server whose system design only reaches the proposed stage of system implementation.